Plasticity in patterns of histone modifications and chromosomal proteins in Drosophila heterochromatin - Riddle, Nicole C.; Minoda, Aki; Kharchenko, Peter V.; Alekseyenko, Artyom A.; Schwartz, Yuri B.; Tolstorukov, Michael Y.; Gorchakov, Andrey A.; Jaffe, Jacob D.; Kennedy, Cameron; Linder-Basso, Daniela; Peach, Sally E.; Shanower, Gregory; et al. (Genome Research, 2011)
Eukaryotic genomes are packaged in two basic forms, euchromatin and heterochromatin. We have examined the composition and organization of Drosophila melanogaster heterochromatin in different cell types using ChIP-array analysis of histone modifications and chromosomal proteins. As anticipated, the pericentric heterochromatin and chromosome 4 are on average enriched for the “silencing” marks H3K9me2, H3K9me3, HP1a, and SU(VAR)3-9, and are generally depleted for marks associated with active transcription. The locations of the euchromatin–heterochromatin borders identified by these marks are similar in animal tissues and most cell lines, although the amount of heterochromatin is variable in some cell lines. Combinatorial analysis of chromatin patterns reveals distinct profiles for euchromatin, pericentric heterochromatin, and the 4th chromosome. Both silent and active protein-coding genes in heterochromatin display complex patterns of chromosomal proteins and histone modifications; a majority of the active genes exhibit both “activation” marks (e.g., H3K4me3 and H3K36me3) and “silencing” marks (e.g., H3K9me2 and HP1a). The hallmark of active genes in heterochromatic domains appears to be a loss of H3K9 methylation at the transcription start site. We also observe complex epigenomic profiles of intergenic regions, repeated transposable element (TE) sequences, and genes in the heterochromatic extensions. An unexpectedly large fraction of sequences in the euchromatic chromosome arms exhibits a heterochromatic chromatin signature, which differs in size, position, and impact on gene expression among cell types. We conclude that patterns of heterochromatin/euchromatin packaging show greater complexity and plasticity than anticipated. This comprehensive analysis provides a foundation for future studies of gene activity and chromosomal functions that are influenced by or dependent upon heterochromatin.
10.1101/gr.110098.110